2011
DOI: 10.5588/ijtld.10.0494
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary paragonimiasis mimicking lung cancer in a tertiary referral centre in Korea

Abstract: Pulmonary paragonimiasis presenting with nodular or mass lesions on CXR is common. Clinicians should therefore include pulmonary paragonimiasis in the differential diagnosis of asymptomatic nodular lesions in the lung in patients who have lived in or travelled to paragonimiasis-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…Especially, eosinophilia may serve as an important parameter leading to the suspicion of paragonimiasis in the differential diagnosis because of its relatively high sensitivity5,7. Our patient, however, didn't have serum and sputum eosinophilia.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Especially, eosinophilia may serve as an important parameter leading to the suspicion of paragonimiasis in the differential diagnosis because of its relatively high sensitivity5,7. Our patient, however, didn't have serum and sputum eosinophilia.…”
Section: Discussionmentioning
confidence: 66%
“…A report by Kim et al7 suggested that the main features of chest CT scans of pleuropulmonary paragonimiasis were pulmonary nodules, including multiple nodules. Since these clinical manifestations and the radiological appearance of paragonimiasis are similar to those of TB or lung malignancy, the diagnosis is often confused, leading to improper and inadequate treatment3,5,8,9,10,11. In the present case, the lesion of mass-like consolidation with cavitation in the upper lobe led us to consider the findings as reactivated pulmonary TB.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations